1997
DOI: 10.1590/s0104-66321997000200008
|View full text |Cite
|
Sign up to set email alerts
|

Application of an Experimental Methodology in the Optimization of a Tungsten Concentration Process by Microemulsions

Abstract: - In this work, we applied an experimental planning methodology in order to correlate the necessary amounts with the description of the a tungsten extraction process by microemulsions. The result is a mathematical modelling carried out using the Sheffe Net method, where the mixtures concentration values are represented inside an equilateral triangle. The tungsten concentration process occurs in two stages: extraction and reextraction. The extraction stage was determined by monitoring: phase relative volume (Vr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…Results with P < 0.05 were considered statistically significant. 15 Table 1. From Table 1, the solubility of the derivatives (<7.5) was higher than that of chitosan (<6.5), and the lowest yield was 75.54%.…”
Section: Antifungal Assaysmentioning
confidence: 99%
“…Results with P < 0.05 were considered statistically significant. 15 Table 1. From Table 1, the solubility of the derivatives (<7.5) was higher than that of chitosan (<6.5), and the lowest yield was 75.54%.…”
Section: Antifungal Assaysmentioning
confidence: 99%
“…E. coli and P. aeruginosa are typical Gramnegative bacteria, the cell wall of which is made up of a thin membrane of peptidoglycan and an outer membrane constituted of lipopolysaccharide, lipoprotein, and phospholipids. 25 Chitosan and its derivatives with large molecular weight can be expected to coat the cell surface and prevent the leakage of intracellular components. Helander et al 12 have shown that chitosan disrupted the barrier properties of the outer membrane of Gram-negative bacteria, as chitosan is protonated at acidic conditions and the carboxyl and phosphate groups of the bacterial surface are anionic and offer potential sites for electrostatic binding.…”
mentioning
confidence: 99%
“…Among the various new methods, the application of microemulsions is one of the most exciting and promising techniques 12 being used in separation, concentration and purification of proteins, extraction of metals, 13,14 adsorption of metals, 15,16 concentration of metals, 17 mineral flotation, 18 etc.…”
mentioning
confidence: 99%